Sustaining national food security and increasing farmers’ income through quality seed - CHAUHAN, J S; CHOUDHURY, P R; PAL, S; SINGH, K H (The Indian Journal of Agricultural Sciences, 2021)
Since independence, India achieved a distinction from ship-to-mouth status to self dependent, food surplus and net exporter of food grains in 69 years and recorded an all time high (285.2 million tonnes) production during 2018-19 from meagre 50.8 mt during 1950-51. In spite of spectacular success in food production over the years, it is a great challenge to sustain high production as well as enhance it further to meet the future requirement, as the population continues to grow steadily with an annual growth rate of 1.10% and expected to be 1.42 billion and 1.48 billion by 2025 and 2030, respectively, from 1.32 billion during 2017; coupled with enhanced consumption of food grains due to rising income, necessitating an increase of 4.5% and 15.7% by 2020 and 2030, respectively, over the present food production. It is a great challenge in view of climate change, diminishing and degrading land and water resources, increasing biotic and abiotic stresses and loss of bio-diversity. The present paper discusses the trend of production and productivity of food crops from 1950-51 to 2018-19; assess the contribution of seed to food production, seed chain, quality seed production and scope of quality seed for enhancing farmers’ income and future strategies for seed research, production and development to sustain food production. Requisite assets such as a strong crop specific cultivar development programmes, 850 high yielding food crop varieties comprising 657 of cereals and 193 of pulses released during the last six years, robust and vibrant seed systems, quality regulatory mechanism, globally competitive seed sector and the largest arable land with 46 soil types across 15 agro-climatic zones favouring seed production of diverse crops are available for sustaining high food production and meet the future demand for seed and food. Ensuring availability of quality seed in adequate quantity though imperative, yet, itself is not enough to trigger the production if it is not coupled with achieving sufficient varietal diversity in seed chain preferably phasing out gradually the old and obsolete varieties and inducting recently developed high yielding and disease resistant varieties. The overall progress and outcome are largely dependent on Government policies and support, which require consistent and adequate financial resources for sustaining a vibrant seed production, farm power machinery, processing units, storage, seed testing, delivery systems and trained human resources besides remunerative prices to the farmers.